2010
DOI: 10.1371/journal.pone.0009159
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Stimulation of Growth Hormone-Releasing Hormone Neurons Is Direct in the Arcuate Nucleus

Abstract: BackgroundGhrelin targets the arcuate nucleus, from where growth hormone releasing hormone (GHRH) neurones trigger GH secretion. This hypothalamic nucleus also contains neuropeptide Y (NPY) neurons which play a master role in the effect of ghrelin on feeding. Interestingly, connections between NPY and GHRH neurons have been reported, leading to the hypothesis that the GH axis and the feeding circuits might be co-regulated by ghrelin.Principal FindingsHere, we show that ghrelin stimulates the firing rate of ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
46
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 76 publications
(179 reference statements)
4
46
1
2
Order By: Relevance
“…The KCNQ/M-current deactivation kinetics features KCNQ2 channels that have been shown to be expressed in nigral dopaminergic neurons 15,18 . In addition, although previous studies have shown that the signal transduction pathway for ghrelin is mediated by PLC/PKC in non-neuronal tissues and cell lines 13,27,28 , our findings first demonstrated that PKC is involved in the effects of ghrelin in native neurons. The signalling transduction pathway of how ghrelin promotes nigral neuronal firing is summarized in Supplementary Fig.…”
Section: Inhibition Of Voltage-dependent Kcnq/m-currents By Ghrelincontrasting
confidence: 48%
See 3 more Smart Citations
“…The KCNQ/M-current deactivation kinetics features KCNQ2 channels that have been shown to be expressed in nigral dopaminergic neurons 15,18 . In addition, although previous studies have shown that the signal transduction pathway for ghrelin is mediated by PLC/PKC in non-neuronal tissues and cell lines 13,27,28 , our findings first demonstrated that PKC is involved in the effects of ghrelin in native neurons. The signalling transduction pathway of how ghrelin promotes nigral neuronal firing is summarized in Supplementary Fig.…”
Section: Inhibition Of Voltage-dependent Kcnq/m-currents By Ghrelincontrasting
confidence: 48%
“…To identify the downstream effector for ghrelin-mediated effect on excitability of nigral dopaminerigc neurons, we hypothesized that ghrelin might affect neuronal Kv7/ KCNQ/M-channels that are predominantly expressed in the CNS and have a profound effect on membrane excitability 32,33 . This hypothesis was based on observations that the pathway activated by binding of ghrelin to its G-protein-coupled receptor GHS-R1a regulates the activation of downstream PLC that depletes membrane PIP 2 levels 13 and activates PKC. The depletion of PIP 2 or phosphorylation of KCNQ channels by PKC can lead to a suppression of neuronal voltage-gated Kv7/KCNQ/M-channel activity 24 .…”
Section: Inhibition Of Voltage-dependent Kcnq/m-currents By Ghrelinmentioning
confidence: 99%
See 2 more Smart Citations
“…This has led to the conclusion that the sexually dimorphic control of GH patterns reflects sex differences in GHRH and somatostatin inputs to the pituitary gland. Acute changes in gonadal steroid environment drastically alter the patterns of GH pulsatility in adulthood (7,8); however, although they receive sexually dimorphic inputs (9,10), GHRH neurons do not display sex-specific electrical characteristics (9,11). We have previously shown that GH cells in the male mouse pituitary gland form an extensive homotypic cell network with an architecture that exhibits marked plasticity during sexual maturation and that can be altered by gonadectomy (12).…”
mentioning
confidence: 99%